Evaluation of ultrasonic phased array system with aluminum specimens - Seet, Qi Yao. (2009)
This paper evaluates the capabilities of M2M MultiX LF system with a linear phased array probe. Tests were carried out on aluminum specimen with various depths, sizes and types of defects and the results are presented here. Ultrasonic phased array is a relatively new technology that has only recently seen an increased usage in many industries, including the aerospace field where it is being used for nondestructive testing of aircraft components. A phased array probe contains many small elements, each of which can be individually pulsed. By apply time delays to the pulsing of the elements, the resultant beam can be steered and focus as desired. The phased array system is found to be able to present more results at one single time. It is able to display the A-scan and B-scan from each of the 16 elements. This speeds up greatly the testing process, as compared to a conventional single-element probe. The dimensions of the test specimens can be profiled by taking advantage of this capability. Depth and size of flat-bottomed holes can be accurately measured with the phased array probe. The C-scans in particular can show the depth and size differences in one image. The depth and size of side-drilled holes are a bigger challenge. There are discrepancies in the results due to the more complex geometry. Empirical equations have been developed though that can calculate the depth and size accurately. Phased array can also detect fine cracks on the surface and under the surface. The capability to do S-scan offer better data interpretation than the conventional displays. It can scan across a larger area and can detect defects that are oriented in a position that is hard to detect. Fabricated test specimen shows that the S-scan is only useful up to an angle of ±50°. The changes in beam profile with the number of active elements are also plotted in 3-D diagrams. It is proven that there is an optimum number of active elements in a probe that can minimize error in defect sizing. The 2 dB amplitude drop technique is the best for sizing of flat-bottomed holes. Studies into the energy profile also revealed some non-ideal behavior that has to be taken note of in future work on the probe.